1985
DOI: 10.1111/j.1365-2125.1985.tb05148.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nicardipine on blood pressure, renal function and plasma aldosterone in normotensive volunteers.

Abstract: 1 The influence of the calcium antagonist nicardipine on intrarenal sodium handling and angiotensin II induced secretion of aldosterone was investigated in 18 normotensive volunteers after the first dose and after 1 week of treatment (20 mg three times daily). 2 A short-lasting natriuresis was observed, which was caused by a decreased reabsorption of sodium localised in both proximal and distal tubules. 3 Log plasma renin activity (PRA) fell significantly on each day during angiotensin II infusion, while log p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Studies of Van Schaik and coworkers suggest that in hypertensive subjects, the natriuresis is mediated by altered renal haemodynamics (Van Schaik et al, 1984). However, other observations, including changes in solute free water excretion and osmolar clearance, implicate a direct effect of nicardipine on proximal tubular function (Young et al, 1985;Van Schaik et al, 1985). Studies with nitrendipine, a related calcium channel blocker, have demonstrated a phosphaturic effect and an increased solute free water excretion, independent of changes in glomerular filtration (Wallia et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Van Schaik and coworkers suggest that in hypertensive subjects, the natriuresis is mediated by altered renal haemodynamics (Van Schaik et al, 1984). However, other observations, including changes in solute free water excretion and osmolar clearance, implicate a direct effect of nicardipine on proximal tubular function (Young et al, 1985;Van Schaik et al, 1985). Studies with nitrendipine, a related calcium channel blocker, have demonstrated a phosphaturic effect and an increased solute free water excretion, independent of changes in glomerular filtration (Wallia et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Neither drug caused significant changes in the total body composition of sodium, potassium, chlorine, calcium, phosphorus or nitrogen at 12 weeks of treatment. Thus the early natriuresis which has been reported with nicardipine use (Van Schaik et al, 1985;Young et al, 1985) is not followed by a significant long-term sodium deficit. This is in contrast to other antihypertensive agents such as angiotensin converting enzyme inhibitors, which also promote an early natriuresis, but in addition may sustain a modest deficit of body sodium content with continued therapy (Hodsman et al, 1983;Sanchez et al, 1985).…”
Section: Discussionmentioning
confidence: 84%
“…Several types of antihypertensive agent, notably a-methyldopa (Birkenhager et al, 1978) and various vasodilators (Hansson, 1983), cause sodium and water retention, and this can limit their antihypertensive effect (so-called 'false tolerance ';Birkenhiiger et al, 1978). By contrast, an early modest natriuresis and diuresis has been reported with some calcium antagonists including nicardipine (Leonetti et al, 1982;Thananopavarn et al, 1984;Van Schaik et al, 1985;Young et al, 1985), and this might enhance the ability of these agents to lower blood pressure. An important aim of the present trial was to examine the extent to which a sodium deficit might be sustained during 3 months' treatment with nicardipine.…”
Section: Introductionmentioning
confidence: 94%
“…In two small studies in hypertensive patients it was reported that nicardipine (Takabatake et al, 1982) and nifedipine (Murphy et al, 1983) produced a reduction in serum potassium of approximately 0.1 and 0.3 mmol P`respectively. This may possibly be attributed to an effect of these agents on renal vasculature giving rise to increased urinary sodium and potassium excretion (Van Schaik et al, 1985, Young et al, 1985. However, the majority of studies to date and the large scale experience with both nicardipine (Syntex, 1986) and nifedipine (Sorkin et al, 1985) have not shown any consistent fall in serum potassium and significant hypokalaemia has not to date been reported.…”
Section: Potassiummentioning
confidence: 99%